Metal Sulfides as a New Class of Sensing Materials. (2015) - Guidi, V.; Fabbri, B.; Gaiardo, A.; Gherardi, S.; Giberti, A.; Malagù, C.; Zonta, G.; Bellutti, P.
Abstract: In the recent years, metal sulfide nanostructured materials have become established in different research fields thanks to their excellent properties. Among the potential applications, metal sulfides may have a high standing role for gas sensing, in which, despite the wide assortment of sensing materials, still metal-oxides maintain a leading role because of their high sensitivity, low cost, small dimensions and simple integration. Experimentation carried out in this work with CdS and SnS2 thick film sensors has showed an unexpected improvements of the chemoresistive properties with respect to their oxides counterparts, in particular toward selectivity to specific compounds, stability and the possibility to operate at room temperature. This opens towards the study of a novel class of sensing materials, which may solve the constant drift of the signal suffered by metal-oxides and ascribed to the in/out diffusion of oxygen vacancies, which alters the doping level.